William Shakespeare - Seltzer, Richard (Massachussetts B%R Samizdat Express, 2003)
This CD-ROM contains, in plain text format, plays and poetry, as well as essays about, William Shakespeare.
Plays - the Mobey electronic edition -- Plays - the first folio -- Plays attributed in part to Shakespeare -- Poetry -- Shakespeare in German translation -- Related materials.
Keywords: Shakespeare, William -- 1564-1616.; Shakespeare, William -- Criticism and interpretation; Shakespeare, William -- Translations into German; English drama